Answer:
x=1
y=2
z=-1
Explanation:
Add the first two equations: (this will be equation 4)
![3y - z = 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iw3b3szkrdt6y86fbhnel13v3kbgepmpa0.png)
Multiply the first equation by 2:
![2x + 2y - 4z = 10](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jsb2i9f7u7791uxin9acy7npqhdw3mc7u4.png)
Take the third equation and subtract the above equation.
![y + 3z = - 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v0nps8y7ibjvopil63cqi020vd154zbarr.png)
Multiply that by 3:
![3y + 9z = - 3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rh2sj0h9dyzaykh8hyk6trgcnfb9n16uee.png)
Subtract equation 4:
![10z = - 10](https://img.qammunity.org/2020/formulas/mathematics/middle-school/azqp80oimo2vwunno4c1gnqkbqskev4pnk.png)
![z = - 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kwl70sul8y3471pjuatikkvk3w67i167vd.png)
For y+3z=-1, plug in values:
![y + 3( - 1) = - 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/89hzfz6r13klcpax8s30654m85ddt7aueb.png)
![y - 3 = - 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/96h4yytwadekhf3rofsywxi5i8jnc44p50.png)
![y = 2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5y42wc6ogpkf35oxmmrrzcklsqb9b714mu.png)
Plug in y and z values in first equation:
![x + 2 - 2( - 1) = 5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xepp9d90mr5p4l3e9f3w6tvfeyja3f55v6.png)
![x + 2 + 2 = 5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/31vh0vdanwqkakd0ajpf5siysr3wys7b1t.png)
![x = 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f94zyyoq5pguxleii2lctl83hdz0s0bme0.png)